An exploratory study of dialectical behaviour therapy for emotional dysregulation and challenging behaviours after acquired brain injury. - Kuppelin, Marie; Goetsch, Antoine; Choisel, Régine; Isner-Horobeti, Marie-Eve; Goetsch, Thibaut; Krasny-Pacini, Agata (NeuroRehabilitation, 2024)
BACKGROUND: Challenging behaviours and emotional dysregulation are common sequelae of acquired brain injury (ABI), but treatment remain underdeveloped. Dialectical behaviour therapy is an evidence-based therapy for emotional dysregulation. OBJECTIVE: To explore the feasibility and preliminary efficacy of dialectical behaviour therapy for ABI. METHODS: An exploratory longitudinal study that compared thirty adults with brain injury presenting persistent emotion dysregulation or challenging behaviours. Control group received a personalized multidisciplinary program only (n = 13). The dialectical behaviour therapy group received five months of emotion regulation skills learning as an add-on (n = 17). Preliminary efficacy was measured on Difficulties in Emotion Regulation Scale-16 and Quality of Life after Brain Injury total score and emotion subscore. RESULTS: Fourteen participants completed the dialectical behaviour therapy. This study provided preliminary evidence for the feasibility and acceptability of dialectical behaviour therapy. Repeated measures revealed improvement on the Difficulties in Emotion Regulation Scale-16 (–7.6 [–17.3; 1.7]; Pr = 0.95) and on the Quality Of Life emotion subscore (13.5 [–3.8; 30.9]; Pr = 0.94). CONCLUSION: This study raises important questions regarding the type of patients who can benefit from this intervention, necessary adaptations of dialectical behaviour therapy and the way it can help post-traumatic growth and identity reconstruction after ABI.